THE GATEWAYS TO ETERNITY: EXPLORING THE EVOLUTION AND SIGNIFICANCE OF MUGHAL TOMBS GATEWAYS IN LAHORE - Kashif, Sumbal; Shahid, Sania; Zulfiqar, Zain; Rafi Khan, Wasim; Zulfiqar, Saba (Journal of Arts & Social Sciences, 2025)
Mughal Architecture, exemplified by its funerary tombs, echoes the memory of its powerful monarchy. Mughal tomb architecture evolved to symbolize the transition from worldly life to the spiritual realm, with gateways framing sacred gardens inspired by Quranic descriptions of paradise. These elaborate gateways have been key elements in Mughal tombs from Akbar’s reign through Aurangzeb’s period. This paper explores the architectural evolution of gateways in Mughal tombs, focusing on the tombs constructed in Lahore during the reigns from Akbar to Aurangzeb (1556-1707) to identify surviving gateways and those that have disappeared. Two case studies, the gateways of Jahangir’s tomb and Nawankot Monument are selected to conduct comparative analysis of their forms through site visits and visual assessments. This research reveals distinct contrast in forms and decorations and calls attention to the urgent need for preservation efforts for future appreciation.